SELAINNYA PEMAHAMAN ATAU YANG MELAMPAUI KEYAKINAN: AYUB DAN EKSES PENDERITAAN - Yasintus T. Runesi (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2021)
In biblical wisdom-literature, there is one fundamental point which states that fear of the Lord, that is wisdom; and eschewed evil is understanding. Someone who follows and practiced these instructions will be blessed by God. This view assumes a relationship between divine law and suffering. However, Job’s suffering in the Book of Job is a kind of counternarrative against this dominant worldview, that suffering is divine judgment on sinful human behavior. According to this understanding, I will explain in this article that Job’s suffering is a story of purification and the ladder of human soul. The cycles of speeches between Job and his friends shows to us that suffering always excessive to the eyes of mind, suffering always exceeds the human ability to understand it completely through our conceptual categories. If we receive suffering with appropriate inner disposition, it is capable of elevating human soul beyond this worldly reality.